Assessment of oral health in chronic kidney disease patients aged between 30-70 years in Mangalore, South India - R. J., Ancy; Shenoy, Rekha P.; Jodalli, Praveen S.; Sonde, Laxminarayan; M., Imran Pasha (International Journal Of Community Medicine And Public Health, 2020)
Background: Chronic kidney disease (CKD) is an increasing health concern worldwide. In addition to systemic changes, kidney disease patients also present with oral complications. The objectives of the study were to assess and compare the oral health status in patients with CKD (with diabetes and without diabetes) undergoing dialysis and not undergoing dialysis aged between (30-70) years and controls in Mangalore, South India. Methods: A descriptive cross-sectional study was conducted among 160 adults with various types of kidney disease and controls, attending a tertiary care hospital in Mangalore. Oral health status was assessed using WHO oral health assessment form for adults 2013. Oral hygiene was assessed by using simplified oral hygiene index and gingival status was assessed by using modified gingival index. Results: Number of decayed teeth was more among controls, and number of missing teeth was more among CKD patients. Diabetic CKD patients who were not on dialysis had highest number of teeth with periodontal pocket and more sextants with loss of attachment. Non-diabetic CKD patients who were on dialysis had more gingival bleeding and gingival inflammation. Multinomial logistic regression analysis showed that CKD patients have more odds of having poor oral health than controls. Conclusions: CKD patients had poor oral hygiene, gingival and periodontal status. In contrast, dental caries was significantly lower in CKD patients than the control group. Good oral health condition mitigates the risk of infection, contributing to a better quality of life among CKD patients.